Reading Du Fu : Nine Views - Tian, Xiaofei (Book collections on Project MUSE., 2020)
This is the first collection of essays in English, contributed by well-known experts of Chinese literature as well as scholars of a younger generation, dedicated to the poetry of Du Fu, commonly regarded as the greatest Chinese poet. These essays are engaged in historically nuanced close reading of Du Fu's poems, both canonical and less known, from new angles and in various contexts, and discuss a series of critical issues, including the local and the imperial; the body politic and the individual body; poetry and geography; perspectives on the complicated relation of religion and literature; m.